The Role of Organizational Culture and Leadership in Improving Hospital Employee Performance: Literature Review - Nur Indah Rahma Dilla; Zahra Andini; Nur Atifah; Selvia Ramadani; Wasiyem (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Organizational culture and leadership play pivotal roles in determining employee performance, particularly in hospitals where effective teamwork and motivation are essential. This study aims to evaluate how organizational culture and leadership styles influence employee performance through a literature review methodology. Relevant articles were sourced from databases such as Google Scholar and Garuda, focusing on publications from the last five years using keywords such as "organizational culture," "leadership," "employee commitment," and "hospital." Findings indicate that a robust organizational culture emphasizing collaboration, innovation, and patient orientation significantly enhances employee commitment and productivity. Furthermore, transformational leadership fosters a positive work environment and boosts motivation, which are critical for maintaining high performance in demanding hospital settings. This study concludes that the synergy between organizational culture and effective leadership can significantly improve employee performance, thereby enhancing healthcare quality. It is recommended that hospitals strengthen cultural values, invest in leadership training, and prioritize employee motivation to achieve organizational goals optimally.